2004
DOI: 10.1021/bc049977+
|View full text |Cite
|
Sign up to set email alerts
|

3‘-Methylphosphonate-Modified Oligo-2‘-O-methylribonucleotides and Their Tat Peptide Conjugates:  Uptake and Stability in Mouse Fibroblasts in Culture

Abstract: Antisense oligo-2'-O-methylribonucleotides and their methylphosphonate derivatives show high binding affinities for their complementary targets under essentially physiological conditions. Additionally, the methylphosphonate linkage is resistant to nuclease hydrolysis. Here we show that a single methylphosphonate internucleotide linkage at the 3'-end of an oligo-2'-O-methylribonucleotide is sufficient to prevent degradation by the 3'-exonuclease activity found in mammalian serum. Complexes formed between a cati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Simple peptide conjugates of oligonucleotides can be prepared in high yield and purified by RP–HPLC (30). However, cationic peptides (including many well-known CPPs) associate with negatively charged phosphodiester or phosphorothioate oligonucleotides and cause precipitation, especially when excess peptide is used to drive the reaction to completion (25,38,39). To overcome this problem, Vivès and Lebleu reported that a Tat peptide could be coupled to a deoxyoligonucleotide in the presence of 0.4 M potassium chloride solution and 40% acetonitrile to maintain solubility (38).…”
Section: Resultsmentioning
confidence: 99%
“…Simple peptide conjugates of oligonucleotides can be prepared in high yield and purified by RP–HPLC (30). However, cationic peptides (including many well-known CPPs) associate with negatively charged phosphodiester or phosphorothioate oligonucleotides and cause precipitation, especially when excess peptide is used to drive the reaction to completion (25,38,39). To overcome this problem, Vivès and Lebleu reported that a Tat peptide could be coupled to a deoxyoligonucleotide in the presence of 0.4 M potassium chloride solution and 40% acetonitrile to maintain solubility (38).…”
Section: Resultsmentioning
confidence: 99%
“…Another useful fragment conjugation method in solution involves oxime formation [82][83][84][85] (Fig. (9)).…”
Section: Synthetic Methodologiesmentioning
confidence: 99%
“…A serious issue in the synthesis of oligonucleotide-based conjugates with highly cationic (positively charged) peptides, which includes many CPPs, is that simple mixing of an oligonucleotide and a cationic peptide may lead to irreversible precipitation of the resultant conjugate and/or complex [65,85]. To overcome the problem, organic co-solvents [65] or non-ionic denaturing agents need to be added [63,66,69].…”
Section: Synthetic Methodologiesmentioning
confidence: 99%
“…Also mouse cell lines are quite often used, e.g. B16 -melanoma cell line [40], RAW264.7 -monocyte macrophage cell line [79], L929 -fibroblast cells [83], or MCA207 -chemically induced murine fibrosarcoma [40].…”
Section: Preparation Of the Samplementioning
confidence: 99%